2019
DOI: 10.7717/peerj.7188
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of cyanobacteria by reverse transcription quantitative real-time PCR based on expression of Microcystis gene

Abstract: In this study, a SYBR Green quantitative real-time PCR method was established and applied. Relative expression of the synthetic genes from Microcystis gas vesicles (gvpC), algal toxin genes (mcyA), and polysaccharides (espL) from water and sediments of Meiliang Bay and from the center of Lake Taihu were tested from January to June, 2017. Indoor Microcystis aeruginosa was used as the control group. The kit for total RNA extraction in Microcystis was optimized. Results showed that the optimized kit extracted hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Many studies have analyzed the abundance of mcy genes to detect the microcystins levels in water bodies [14,15]. The SYBR Green qPCR method is characterized by high speci city, reproducibility, rapidity, and has been widely used for the quantitative detection of gene expression [16,17]. Anil Kumar et al found the presence of the toxic cyanobacterium by employing polymerase chain reaction (PCR) ampli cation of six genes of the mcy genes cluster (mcyA, mcyB, mcyC, mcyD, mcyE and mcyG) in seven eutrophicated ponds of Varanasi [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have analyzed the abundance of mcy genes to detect the microcystins levels in water bodies [14,15]. The SYBR Green qPCR method is characterized by high speci city, reproducibility, rapidity, and has been widely used for the quantitative detection of gene expression [16,17]. Anil Kumar et al found the presence of the toxic cyanobacterium by employing polymerase chain reaction (PCR) ampli cation of six genes of the mcy genes cluster (mcyA, mcyB, mcyC, mcyD, mcyE and mcyG) in seven eutrophicated ponds of Varanasi [18].…”
Section: Introductionmentioning
confidence: 99%